Analisis de los tres tipos de fermentacion de cacao en la provincia de Los Rios - Robinson Alexis, Jimenez Moya (2021)
Ecuador's cocoa production is becoming one of the most important targets for export businesses. Several international chocolate companies have set their sights on the quality of our country's cocoa. Ecuadorian cocoa is recognized worldwide for its marked characteristics of aroma and color, highly appreciated in the preparation of fine chocolates. The fermentation of cocoa is a very important stage in the processing of the bean, since the biochemical changes that give rise to the aroma and flavor precursors take place. The most commonly used fermenters are piles, pouches and wooden crates. The pile method consists of stacking the fresh cocoa, The sack method, consists of placing the fresh almonds in sacks, but these obtain a lower rate of fermentation, the method in drawers, is used by small and medium producers and this method is very important because it offers many advantages such as an optimal temperature, greater oxygenation, high concentration of aroma and color. Among the three types of fermenters, they were efficient in the fermentation process, since appropriate temperatures and rates of fermentation were reached, however, due to the chemical characteristics obtained in cocoa and for reasons of practical use, handling, the wooden box could be considered as the most suitable type of fermenter.